Talking Stick Learning Model Assisted by Media Question Box: Effectiveness on Science Learning Outcomes in Elementary Schools - Purnama Sari, Bella Yulia; Candra Sayekti, Ika (LPPM Undiksha, 2023)
Science learning is still conventional, causing students to be less focused and get grades in the low category. The research objective was to analyze the effectiveness of using the talking stick learning model assisted by the media questions box on science learning outcomes in elementary schools. This type of quantitative research with experimental design. Selection of the sample using simple random sampling. The research subjects were fifth-grade elementary school. The research design used the